Performance analysis during the 2014 FIFA World Cup Qualification - Flégl, M. (The Open Sports Sciences Journal, 2014)
This article analyzes the performance of the national football teams during the 2014 FIFA World Cup qualification. The sample consists of 31 qualified national teams to the final tournament in Brazil. The analysis uses Data Envelopment Analysis (DEA) methodology and is carried out for the whole qualification period between June 2011 and November 2013. Each national team is evaluated according to a number of played matches, used players, qualification group quality, obtained points, and score. The results show that only 12.9% teams reached the performance of 100%. The reasons of low performances mainly depend on teams´ qualities either in each qualification zone or in each qualification group. In addition, a sensitivity analysis is used to confirm the adequate structure of the DEA model.